APLIKASI PEMETAAN PERGURUAN TINGGI AGAMA ISLAM SWASTA (Studi Kasus: Kopertais Wilayah XII) - Muhammad Jazman; Muhammad Adnil Riza (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2021)
This research aims to design a website-based geographic information system (WebGIS) for mapping privately owned Islamic higher education in the region of Riau and Riau Islands. The phenomena underlying the research is WebGIS has been used to easily inform community about privately-owned Islamic higher education (PTAIS)’ in the region of both Riau Province and Riau Islands Province, Indonesia. KOPERTAIS region XII is the coordinator for the private Islamic colleges. KOPERTAIS is the governing, supervisory institutions, and construction of the PTAIS. WebGIS is designed using the method of Object Oriented Analysis Design (OOAD) tools and Unified Modelling Language (UML). The systems development model is Prototyping. Engineering testing system using the technique Unit Acceptance Testing (UAT). The results of this research is a map of geographic information system of Islamic higher-education in the region of both Riau Province and Riau Islands Province. This system can help prospecting candidates know the information and spread of location of the Islamic higher-education in the region.